A nanozyme-like colorimetric sensing strategy based on persulfate activation on Co-based metal–organic frameworks. Issue 22 (24th February 2023) - Deng, Zehui; Xiao, Qingling; Fu, Heyun; Zheng, Shourong; Alvarez, Pedro J.J.; Zhu, Dongqiang; Xu, Zhaoyi; Qu, Xiaolei
Abstract : This study developed a nanozyme-like colorimetric sensing strategy based on persulfate activation for the first time, outperforming the H2 O2 activation approach. Abstract : A nanozyme-like colorimetric sensing strategy based on persulfate activation on Co-based metal– organic frameworks is developed for biomolecule detection in solution and on paper strips. By switching from H2 O2 activation on nanozymes to catalytic persulfate activation, this general strategy provides higher sensitivity, faster speed, and wider application ranges for detection.